Social media use in patients with acne vulgaris: What do patients expect from social media? - Kayiran, Melek Aslan; Karadag, Ayse Serap; Alyamac, Gokcen; Cemil, Bengu Cevirgen; Demirseren, Duriye Deniz; Aksoy, Hasan; Yazici, Serkan (Wiley, 2021)
Background Acne vulgaris (AV) may affect external appearance and significantly deteriorate the quality of life of patients. Therefore, patients make various inquiries about their disease and seek treatment options. Aims To investigate the social media usage habits of patients with AV concerning their diseases, and their recommendations for dermatologists related to social media use. Methods A total of 1609 patients with AV completed the survey prepared by the authors and the Cardiff Acne Disability Index questionnaire. The Food and Drug Administration severity scores and clinical information of the patients were noted by their physicians. Results Of the 1,489 patients who stated that they used social media, 46.31% regularly and 28.77% sometimes referred to these sources to make inquiries about AV. Social media usage for AV was statistically significantly higher in women, participants with short term and severe disease, those with a moderate income level, and those using topical treatment and cosmetics. They mostly used Google (67%), Instagram (54%), and YouTube (49%). While 76% of the participants stated that they did not share what they saw on the Internet with their doctor. Of the respondents, 18.5% were trying to contact their dermatologists through the Internet, and 69.73% would prefer experts such as dermatologists to post-AV-related content. Conclusions Our study shows that patients frequently resort to social media to seek information about AV. In the changing digital world order, it is observed that there is a need for dermatologists to use social media more actively to share accurate information about AV.
Keywords: acne vulgaris; cosmetic; Internet; social media